Identificação de cultivares de trigo eficientes no uso do nitrogênio utilizando abordagens fisio-moleculares - Milioli, Anderson Simionato (2014)
The identification of wheat genotypes with more nitrogen use efficiency (NUE) is essential to obtain higher yields with lower investments, thereby increasing sustainability and reducing potential environmental impacts caused by excessive use of nitrogenous fertilizers. Several studies have been conducted worldwide to evaluate the NUE in wheat and other crops in different environmental conditions. The objective of this study was to characterize Brazilian wheat cultivars recently developed by research as NUE, through analysis of the leaf chlorophyll index and use of molecular markers, in order to identify an association between these characters. For this, an experiment was conducted in a greenhouse using 12 wheat cultivars and four levels of nitrogen fertilizer (0, 80, 160 and 240 kg N ha-1) in experimental design of randomized blocks with three replicates. Grain yield and chlorophyll index responded positively with increasing nitrogen levels, unlike NUE that showed a decrease with increasing nitrogen levels applied. There was no direct association between the chlorophyll index and molecular markers with the NUE. The EST-SSR marker designed for the enzyme nitrate reductase sequence and the marker designed on the EST encoding the Aquaporin gene showed polymorphism genotypes and divided into two distinct groups, however, the existing polymorphism not allowed to group the cultivars more productive or more NUE, indicating there is a need to test a large number of primers to inferred precisely about this trait.